Karakteristik komposit sandwich dengan inti (core) open cell foam bambu berlubang - P.D. Setyawan; S. Sugiman; S. Sinarep; H. Hilwan (Universitas Mataram, 2023)
The sandwich composite used in this investigation has a bamboo open-cell foam core and a plywood skin. In this study, the density, flatwise compressive strength, flexural strength, and water absorption of sandwich composite materials will be determined. The volume proportion of fiber in the bamboo foam core was 15% in this investigation, and PVAc adhesive was employed. The open-cell foam core has a square-shaped hollow in the center and hole spacings of 30mm, 40mm, and 60mm. The tests included density testing (ASTM C271), flatwise compression testing (ASTM C365-05), flexural testing (ASTM C393), and water absorption testing (ASTM C272). According to the study's findings, compared to sandwich composites with core-opened cell foam without holes, sandwich composites with core-opened cell foam with holes have an average density, an average specific flatwise compressive strength, and an average specific bending strength that are smaller. The percentage of water absorption in the sandwich composite demonstrates the opposite. Comparing the sandwich composite with core-opened cell foam without holes (0.45 g/cm3) to the sandwich composite with core-opened cell foam with holes, the average density of the latter decreased by 6–13%. The decrease in the avarage specific flatwise compressive strength of the sandwich composite with a hollow core was 2-20% compared to the sandwich composite with an open-cell foam core without holes (41.22 MPa/cm3/gr). The average specific bending strength of the sandwich composite with the core opened cell foam with holes was reduced by 40–50% when compared to the sandwich composite with the core opened cell foam without holes (26.38 MPa/cm3/gr).